1970
DOI: 10.1177/002383097001300303
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Normal and Retarded Boys on Berko's Test of Morphology

Abstract: Berko's test of morphology was administered to two groups of educable mentally retarded public school boys who were matched on chronological age and mental age respectively to groups of normal public school boys. Results were analysed using teachers' responses as criteria for " correctness ". In general, neither group of EMRs performed as well as the normal boys. Criticisms of the test on the basis of the obtained results as well as suggestions for modifications and further research needs are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Ofthe nonsense words alone, ninety-six ofthe 101 scored six or less out of a total possible score of thirty; sixty-one out of the 101 failed completely even on the easiest items such as the plural form of "wug". (Dever and Gardner, 1970, point out the great difficulties that even educable retarded children have with nonsense words as compared with lexical words.) This was the test in the battery where easily-established rapport was most in peril; nearly all found the transition from the lexical words to the nonsense words puzzling and the sequence of nonsense items tiring.…”
Section: Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Ofthe nonsense words alone, ninety-six ofthe 101 scored six or less out of a total possible score of thirty; sixty-one out of the 101 failed completely even on the easiest items such as the plural form of "wug". (Dever and Gardner, 1970, point out the great difficulties that even educable retarded children have with nonsense words as compared with lexical words.) This was the test in the battery where easily-established rapport was most in peril; nearly all found the transition from the lexical words to the nonsense words puzzling and the sequence of nonsense items tiring.…”
Section: Reliabilitymentioning
confidence: 99%
“…(In practice, it was found that if the subject could not succeed on at least one lexical item, he would not succeed with any of the nonsense items.) Dever and Gardner (1970) also advocated this practice for retarded children. The correctness of responses was judged by comparing them with those of their teachers or supervisors.…”
Section: A Test Of Morphologymentioning
confidence: 99%
“…'This truck is big, but this truck is .'). Berko (1958) Jarvella & Sinnott (1972, and Ivimey (1975) have used the cloze procedure with nonsense words to elicit morphological structures from normal children; while Lovell & Bradbury (1967) and Dever & Gardner (1970) used the technique with retarded subjects. The latter studies found normal children did better than retarded children on the task, and real words elicited better scores than did nonsense words.…”
Section: Taskmentioning
confidence: 99%
“…El interés por este paradigma experimental ha llevado a querer investigar los efectos de la evocación en niños con diferentes patologías y situaciones diferenciales tales como la sordera (Cooper, 1967), los niños en situación de deprivación social (Shriner y Miner, 1968), los niños con Trastorno Específico de Lenguaje -TEL- (Leonard, 1995;Contreras y Soriano, 2007), los niños con síndrome de Williams (Bromberg, Ullman, Marcus, Kelly y Coppola, 1994), niños con discapacidad intelectual (Dever y Gardner, 1970) y niños con síndrome de Down (Lázaro, Garayzábal y Moraleda, en prensa). Concretamente, los datos normativos del inglés muestran que los niños ingleses con TEL tienen menos problemas con los morfemas gramaticales nominales (genitivo sajón, terminación -s del plural y artículos) que con la morfología flexiva verbal inglesa (Leonard 1995).…”
Section: Introductionunclassified